TRANSFORMASI EKONOMI ISLAM DI TIMUR TENGAH: PERBANDINGAN SAUDI, YAMAN, DAN TURKI - Sapitri, Suci Afrilianti (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2023)
Islamic economics is an alternative economic system in the midst of the development of the economic system of capitalism and socialism. The development of the Islamic economy around the world has been positive and several countries have developed significantly. The development of Islamic economics in the Middle East is experiencing interesting dynamics to observe. The development of the Islamic economy in Saudi Arabia has experienced a significant increase, while in Yemen it tends to stagnate, due to unstable political factors. In Turkey, which is a secular country, the Islamic economy is growing slowly, but recently it has received support from the government and the trust of the people.